Breast MRI at Very Short TE (minTE): Image Analysis of minTE Sequences on Non-Fat-Saturated, Subtracted T1-Weighted Images - Wenkel, Evelyn; Janka, Rolf; Geppert, Christian; Kaemmerer, Nadine; Hartmann, Arndt; Uder, Michael; Hammon, Matthias; Brand, Michael (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose The aim was to evaluate a minimum echo time (minTE) protocol for breast magnetic resonance imaging (MRI) in patients with breast lesions compared to a standard TE (nTE) time protocol.Methods Breasts of 144 women were examined with a 1.5 Tesla MRI scanner. Additionally to the standard gradient-echo sequence with nTE (4.8 ms), a variant with minimum TE (1.2 ms) was used in an interleaved fashion which leads to a better temporal resolution and should reduce the scan time by approximately 50 %. Lesion sizes were measured and the signal-to-noise ratio (SNR) as well as the contrast-to-noise ratio (CNR) were calculated. Subjective confidence was evaluated using a 3-point scale before looking at the nTE sequences (1 = very sure that I can identify a lesion and classify it, 2 = quite sure that I can identify a lesion and classify it, 3 = definitely want to see nTE for final assessment) and the subjective image quality of all examinations was evaluated using a four-grade scale (1 = sharp, 2 = slight blur, 3 = moderate blur and 4 = severe blur/not evaluable) for lesion and skin sharpness. Lesion morphology and contrast enhancement were also evaluated.Results With minTE sequences, no lesion was rated with “definitely want to see nTE sequences for final assessment”. The difference of the longitudinal and transverse diameter did not differ significantly (p > 0.05). With minTE, lesions and skin were rated to be significantly more blurry (p < 0.01 for lesions and p < 0.05 for skin). There was no difference between both sequences with respect to SNR, CNR, lesion morphology, contrast enhancement and detection of multifocal disease.Conclusion Dynamic breast MRI with a minTE protocol is feasible without a major loss of information (SNR, CNR, lesion morphology, contrast enhancement and lesion sizes) and the temporal resolution can be increased by a factor of 2 using minTE sequences.Key points Citation Format
Keywords: breast; technology assessment; MR imaging